(untitled) (Jurnal Bahasa Lingua Scientia, 2023)
The emergence of a modern lifestyle called ’childfree’ goes against the traditional principles and culture of Indonesian society. Practically, this paradigm has led to both positive and negative views from the society. This study aims to identify the attitudinal languages towards childfree discourse through analysing the appraising items as language evaluation. This research uses a qualitative descriptive method. Data collection was carried out by corpus analysis with the help of the UAM Corpus tool. A total of 30 childfree articles on the internet were manually annotated based on Martin and White’s (2005) appraisal scheme. Data analysis will be carried out descriptively by interpreting the annotation results on the corpus tool. The annotation results show that 458 lexical choices are categorised into attitude with 306 appreciations, 105 affects, and 47 judgements. From the total number of attitudes, 304 items showed negative attitudes, 135 positive attitudes, and 19 neutral attitudes. Overall, the appraising items on the 30 childfree discourses in Indonesia were varied. Some discourses have many positive evaluations. However, discourses that construct childfree as negative are more common. In addition to the construction of negative views, the authors also tend to avoid subjectivity by presenting sources of language evaluations from outside of the author.